Lista de plantas leñosas de los bosques estacionalmente secos del valle del Marañón, Perú - Marcelo-Peña, José Luis (2025)
Seasonally dry tropical forests (SDTF) remain woefully understudied despite mounting evidence that they are highly threatened hotspots of biodiversity with large numbers of endemic species. The dry forests of the Marañón river valley in northern Peru is one such hotspot. However, threats to the ecosystem primarily due to agriculture and livestock farming, they are accelerating their de[1]struction, placing the unique species present at high risk. Here we present a preliminary annotated checklist of the woody plants of the dry forest of the Marañón valley, this list includes 413 species and infraspecific taxa, in 223 genera and 59 families. We estimate that 33 % of these taxa are en[1]demic. This list is expected to be incomplete given that large areas of the valley remain unexplored botanically. It is anticipated that this checklist will become a valuable resource for management and conservation of this unique ecosystem, and will act as a stimulus for further botanical exploration.